AN EXTENDED DISCUSSION ON A HIGH-CAPACITY COVERT CHANNEL FOR THE ANDROID OPERATING SYSTEM - Heard, Timothy; Johnson, Daryl (International Journal of Computing, 2016)
In “Exploring a High-Capacity Covert Channel for the Android Operating System” [1], a covert channel for communicating between different applications on the Android operating system was introduced and evaluated. This covert channel proved to be capable of a much higher throughput than any other comparable channels which had been explored previously. This article will expand on the work which was started in [1]. Specifically, further improvements on the initial covert channel concept will be detailed and their impact with regards to channel throughput will be evaluated. In addition, a new protocol for managing connections and communications between collaborating applications purely using this channel will be defined and explored. A number of different potential mechanisms and techniques for detecting the presence and use of this covert channel will also be described and discussed, including possible counter-measures which could be implemented.